Parthenogenetic vs. sexual reproduction in oribatid mite communities. Issue 12 (29th May 2019) - Maraun, Mark; Caruso, Tancredi; Hense, Jonathan; Lehmitz, Ricarda; Mumladze, Levan; Murvanidze, Maka; Nae, Ioana; Schulz, Julia; Seniczak, Anna; Scheu, Stefan
Abstract: The dominance of sex in Metazoa is enigmatic. Sexual species allocate resources to the production of males, while potentially facing negative effects such as the loss of well‐adapted genotypes due to recombination, and exposure to diseases and predators during mating. Two major hypotheses have been put forward to explain the advantages of parthenogenetic versus sexual reproduction in animals, that is, the Red Queen hypothesis and the Tangled Bank/Structured Resource Theory of Sex. The Red Queen hypothesis assumes that antagonistic predator—prey/ parasite–host interactions favor sex. The Structured Resource Theory of Sex predicts sexual reproduction to be favored if resources are in short supply and aggregated in space. In soil, a remarkable number of invertebrates reproduce by parthenogenesis, and this pattern is most pronounced in oribatid mites (Oribatida, Acari). Oribatid mites are abundant in virtually any soil across very different habitats, and include many sexual and parthenogenetic (thelytokous) species. Thereby, they represent an ideal model group to investigate the role of sexual versus parthenogenetic reproduction across different ecosystems and habitats. Here, we compiled data on oribatid mite communities from different ecosystems and habitats across biomes, including tropical rainforests, temperate forests, grasslands, arable fields, salt marshes, bogs, caves, and deadwood. Based on the compiled dataset, we analyzed if the percentage of parthenogenetic species and the percentage of individuals of parthenogenetic species are related to total oribatid mite density, species number, and other potential driving factors of the reproductive mode including altitude and latitude. We then interpret the results in support of either the Red Queen hypothesis or the Structured Resource Theory of Sex. Overall, the data showed that high density of oribatid mites, indicating abundance of resources, is associated with high frequency of parthenogenesis supporting predictions of the Structured Resource Theory of Sex rather than the Red Queen hypothesis. Abstract : We compiled data on oribatid mite communities from different habitats across biomes. Based on the compiled dataset, we analyzed if the percentage of parthenogenetic species and the percentage of individuals of parthenogenetic species are related to total oribatid mite density, species number, and potentially other driving factors of the reproductive mode including altitude and latitude. Overall, the data showed that low density of oribatid mites due to harsh environmental conditions is associated with high frequency of parthenogenesis supporting predictions of the Structured Resource Theory of Sex rather than the Red Queen hypothesis.